Diazonium interface chemistry and click polymerization: A novel route for carbon nanotube‐polytriazole nanocomposites. (28th December 2015) - Bensghaïer, Asma; Salmi, Zakaria; Le Droumaguet, Benjamin; Mekki, Ahmed; Mohamed, Ahmed A.; Beji, Mohamed; Chehimi, Mohamed M.
Abstract : Multiwalled carbon nanotubes (MWCNTs) were modified with azidophenyl groups from the in situ generated 4‐azidobenzenediazonium salt to provide a nanoscale platform for the surface‐confined polyaddition of α‐ω ‐bis (O‐propargyl) diethylene glycol and 1, 3‐diazidopropane. The polyaddition in the presence of the azido‐functionalized MWCNTs (MWCNT‐N3 ) provided robust polytriazole‐grafted MWCNTs (MWCNT‐PTAz) that withstood ultrasonication. The end MWCNT‐PTAz nanocomposite and the reference materials pristine MWCNTs and MWCNT‐N3 were characterized by thermogravimetric analyses, XPS, IR, and Raman. Particularly, N1s XPS spectra aided the detection of azide and triazole rings at the surface of MWCNT‐N3 and PTAz, respectively. The high resolution C1s region from MWCNT‐PTAz clearly exhibits C‐N and C‐O components assigned to the triazole and diethylene glycol repeat units in the PTAz grafts. Examination of the ID /IG peak intensity ratio from Raman spectra indicate true covalent modification of the MWCNTs with diazonium salts. IR spectroscopy tracked the azide to triazole transformation. Thermal analysis indicates a substantial mass loading of the organic grafts levelling off at 37 wt/wt%. This works brings strong supporting evidence for the versatility of diazonium salts in constructing MWCNT‐polymer nanocomposites through polyaddition of clickable diazido and diethynyl dimers at the surface of clickable MWCNTs. Copyright © 2015 John Wiley & Sons, Ltd.